Genomic, transcriptomic and metabolomic analyses of Amorphophallus albus provides insights into the evolution and resistance to southern blight pathogen - Duan, Longfei; Qin, Jianfeng; Zhou, Gaoxin; Shen, Chuan; Qin, Baofu (Frontiers in Plant Science, 2025)
IntroductionAmorphophallus albus, a perennial herb in the Araceae family, is a valuable cash crop known for its high production of konjac glucomannan and high disease resistance.MethodsIn this study, we present a high-quality, chromosome-scale genome assembly of A. albus using a combination of PacBio HiFi sequencing, DNBSEQ short-read sequencing, and Hi-C technology. To elucidate the molecular mechanisms underlying southern blight resistance, we performed an integrated analysis of transcriptomic and metabolomic profiles across three infection stages of A. albus.Results and discussionHere, we assembled and annotated the complete genome of A. albus, providing a chromosome-level assembly with a total genome size of 5.94 Gb and a contig N50 of 5.61 Mb. The A. albus genome comprised 19,908 gene families, including 467 unique families.The slightly larger genome size of A. albus compared to A. konjac may have been affected by a recent whole-genome duplication event. Transcriptional and metabolic analyses revealed significant enrichment of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) involved in phenylpropanoid biosynthesis, plant hormone signal transduction, phenylalanine metabolism, and the biosynthesis of phenylalanine, tyrosine, and tryptophan. These findings not only advance the understanding of genetic and evolutionary characteristics of A. albus but also provide a foundation for future research on the resistance mechanisms of konjac against southern blight disease.